High Performance VLSI Signal Processing: Innovative Architectures and Algorithms - Villagarcía Wanza, Horacio Alfredo (2001)
The book intends to address the important aspects of high-performance signal processing with a focus on the recent development of VLSI technology for signal processing.\nThe editors collect much of all the research efforts and findings that have made high performance implementation of signal processing possible in the last decade in two volumes.